2008
DOI: 10.5694/j.1326-5377.2008.tb01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of evidence to guide primary health care policy and practice to prevent childhood obesity

Abstract: Objectives: To identify key barriers to effective engagement of primary health care (PHC) providers and families in promoting healthy weight among children aged 2–6 years, and to examine promising interventions to identify policy goals to overcome these barriers. Methods: We conducted a literature review of published and unpublished articles from January 1990 to February 2006 using keywords relating to childhood obesity, risk factors, prevention, populations and primary care provider interventions, constraints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
3
22
0
4
Order By: Relevance
“…Several studies have observed that childhood obesity is a sensitive topic because healthcare professionals fear offending parents [17,18,33]. Our study supports these findings.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have observed that childhood obesity is a sensitive topic because healthcare professionals fear offending parents [17,18,33]. Our study supports these findings.…”
Section: Discussionsupporting
confidence: 90%
“…The 23 included studies were delivered through a variety of settings: preschool/childcare, home, group, primary care, and mixed settings. Approximately two‐thirds involved multifaceted interventions ( n = 14) and a similar proportion were conducted in the United States ( n = 15). Just over half of the studies targeted socioeconomically disadvantaged families ( n = 12) and three quarters were published from 2003 onward ( n = 17).…”
Section: Resultsmentioning
confidence: 99%
“…The small number and recency of the early childhood obesity‐prevention literature suggests this is a new and developing research area. A number of reviews of obesity prevention during early childhood have been published in recent years (13,14,15,16,17), all with differing inclusion criteria and predominantly focusing on the preschool age group. The current review was conducted to provide an update of the emerging evidence in this area and to assess the quality of studies reported.…”
Section: Introductionmentioning
confidence: 99%
“… Chronic disease management ( Cranston et al, 6 Dennis et al 7 ); Integration, coordination and multidisciplinary care ( Jackson et al, 8 Mitchell et al, 9 Powell Davies et al 10 ); Innovative models for comprehensive primary health care delivery ( McDonald et al, 11 Naccarella et al, 12 Humphreys et al 13 ); Innovative models for the management of mental health in primary health care settings ( Griffiths and Christensen 14 ); Children and young Australians, health promotion and prevention ( McDonald et al, 15 Hearn et al 16 ); and Workforce (focus on competency‐based training) ( Glasgow et al 17 ). …”
Section: Streammentioning
confidence: 99%